2020
DOI: 10.3389/fcell.2020.571004
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in VWA1, Encoding von Willebrand Factor A Domain-Containing Protein 1, Is Associated With Hemifacial Microsomia

Abstract: Background: Hemifacial microsomia (HFM) is a type of rare congenital syndrome caused by developmental disorders of the first and second pharyngeal arches that occurs in one out of 5,600 live births. There are significant gaps in our knowledge of the pathogenic genes underlying this syndrome. Methods: Whole exome sequencing (WES) was performed on five patients, one asymptomatic carrier, and two marry-in members of a five-generation pedigree. Structure of WARP (product of VWA1) was predicted using the Phyre2 web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 64 publications
3
27
1
Order By: Relevance
“…A heterozygous missense variant was identified by WES analysis in VWA1 gene (c.905G>A, p.Arg302Gln), in a family in which an autosomal dominant form of HFM associated with unilateral or bilateral microtia segregates in five generations 58. Of note, microduplications of VWA1 and PYGO2 were characterised in a patient presenting with mandibulofacial dysostosis and microtia 59 .…”
Section: Aetiologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A heterozygous missense variant was identified by WES analysis in VWA1 gene (c.905G>A, p.Arg302Gln), in a family in which an autosomal dominant form of HFM associated with unilateral or bilateral microtia segregates in five generations 58. Of note, microduplications of VWA1 and PYGO2 were characterised in a patient presenting with mandibulofacial dysostosis and microtia 59 .…”
Section: Aetiologiesmentioning
confidence: 99%
“…VWA1 codes for Von Willebrand factor A domain-containing protein 1 and is associated with an autosomal-recessive neuropathy with myopathic features [MIM:619 216]. The knockdown and knockout of its zebrafish homologue support the involvement of this gene in craniofacial cartilages development, possibly through decrease of cranial neural crest cells proliferation 58…”
Section: Aetiologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorlin and Pindborg first introduced the term HFM in 1964 (63). HFM is a congenital disorder caused by developmental disorders of the first and second pharyngeal arches that mainly affect the jaws, ears, facial soft tissue, orbits, and facial nerve function (64). HFM is the second most common congenital disorder of the face following CL and palate: the incidence is estimated to be in 1:3,000 to 1:5,000 live births.…”
Section: Hemifacial Microsomia (Hfm)mentioning
confidence: 99%
“…Recently, Timberlake et al reported SF3B2 as the most frequent gene involved in OAVS 16. Before Timberlake et al , various publications also reported five other genes in OAVS individuals: ZYG11B ,17 EYA3 ,18 VWA1 ,19 ZIC3 20 and AMIGO2 21. A large set of copy number variations (CNVs) has also been reported in the literature in patients with OAVS 4 22.…”
Section: Introductionmentioning
confidence: 99%